2019
DOI: 10.1016/j.ccell.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer Convergence to a Small-Cell Neuroendocrine Phenotype that Shares Susceptibilities with Hematological Malignancies

Abstract: Small-cell neuroendocrine cancers (SCNCs) are an aggressive cancer subtype. Transdifferentiation toward an SCN phenotype has been reported as a resistance route in response to targeted therapies. Here, we identified a convergence to an SCN state that is widespread across epithelial cancers and is associated with poor prognosis. More broadly, non-SCN metastases have higher expression of SCN-associated transcription factors than non-SCN primary tumors. Drug sensitivity and gene dependency screens demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 78 publications
14
121
0
Order By: Relevance
“…Consistent with our findings, a recent study identified sensitivity to inhibition of the cholesterol biosynthetic pathway enzyme squalene epoxidase in SCLC cells (53). A large meta-analysis of small cell neuroendocrine tumors also suggests susceptibility to disruption of lipid and sterol metabolism (54). Additional investigation into the latter will need to be performed to ascertain which of the many roles of the mevalonate pathway and its byproducts are truly critical in SCLC.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with our findings, a recent study identified sensitivity to inhibition of the cholesterol biosynthetic pathway enzyme squalene epoxidase in SCLC cells (53). A large meta-analysis of small cell neuroendocrine tumors also suggests susceptibility to disruption of lipid and sterol metabolism (54). Additional investigation into the latter will need to be performed to ascertain which of the many roles of the mevalonate pathway and its byproducts are truly critical in SCLC.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study identified “SCLC-like” epithelial tumors in pan-cancer samples using a principal component analysis-based approach. They found that tumors across many lineages with a higher “SCLC-like” score had lower immune gene expression (49). We applied our NE scoring method across all cancer lineages (“pan-cancer” analysis) to compute NE scores and assess their relationship with immune phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Its targets were opposing altered in inflamed TME in part of tumors( Figure.4C), including neurogenesis-related genes: CHRNB2, neuronatin (NNAT), neuronal pentraxin 1 (NPTX1), extracellular matrix organization: CAPN6, KRT6A; cellular traffic: KIF1A, SLC34A2( Figure.4A, D). These results revealed that miR-650 may be involved the formation of neuroendocrine phenotype of non-inflamed TME by inhibiting the expression of neurogenesisrelated genes [17].…”
Section: Figure3mentioning
confidence: 86%